2009
DOI: 10.1080/13632460902813216
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Assessment of an Innovative Isolation Bearing System with Shape Memory Alloys

Abstract: The objective of this work is to investigate the feasibility of a new seismic isolation device concept based on the superelastic effect given by shape memory alloys. Seismic isolation is one of the most effective options for passive protection of structure, which modifies the global response and improves performances, in particular regularizing the structural response, shifting the fundamental period of vibration, and increasing the global energy dissipation. Shape memory alloys (SMAs) are characterized by uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
38
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 9 publications
0
38
0
Order By: Relevance
“…A number of researchers have explored the potential application of superelastic SMAs in a seismic isolation system (Jalali et al 15 ; Ozbulut and Hurlebaus [16][17][18][19] ; Bhuiyan and Alam 20 ; Gur et al 21 ). Attanasi et al 22 conducted an analytical study to investigate the feasibility of isolation systems with SMAs. They found that an isolation system that relies solely on SMAs for energy dissipation provides less favorable seismic performance than isolation system with bilinear force-deformation characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…A number of researchers have explored the potential application of superelastic SMAs in a seismic isolation system (Jalali et al 15 ; Ozbulut and Hurlebaus [16][17][18][19] ; Bhuiyan and Alam 20 ; Gur et al 21 ). Attanasi et al 22 conducted an analytical study to investigate the feasibility of isolation systems with SMAs. They found that an isolation system that relies solely on SMAs for energy dissipation provides less favorable seismic performance than isolation system with bilinear force-deformation characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, recentering friction-based isolation systems have been proposed based on the coupling between Flat Sliding Bearings (FSBs) and auxiliary Shape Memory Alloy (SMA) devices [Song et al, 2006;Cardone et al, 2003Cardone et al, , 2006Casciati et al, 2007;Attanasi et al, 2009].…”
Section: Introductionmentioning
confidence: 99%
“…A number of researchers have explored the potential application of superelastic SMAs in a seismic isolation system (Jalali et al, 2011;Ozbulut and Hurlebaus, 2010a, 2011a, 2011b, 2012Rahman Bhuiyan, A., and Alam, 2013;Gur et al, 2013) . Attanasi et al (2009) conducted an analytical study to investigate the feasibility of isolation systems with SMAs. They found that an isolation system that relies solely on SMAs for energy dissipation provides less favorable seismic performance than isolation system with bilinear force-deformation characteristics.…”
Section: Introductionmentioning
confidence: 99%